Análise dos fatores influentes sobre o crescimento de ipê – roxo (Handroanthus heptaphyllus Vell. (Mattos)) – um estudo de caso - Schröder, Thomas (2017)
Red Lapacho is timber species with largest market value, considered along with Mahogany, as 'green gold' in areas of natural forest logging. Therefore, the objective of this study was to analyze the different factors that influence the growth of this species, taking into consideration the spatial and temporal dependence inherent to the data. A census of Red Lapacho individuals was carried out in a natural fragment of Subtropical Deciduous Forest with approximately 13 hectares of area. Quantitative morphological and diameter increment data were obtained for each tree of this species. Competitors defined by Bitterlich plots were measured and identified, and a regular grid with infill points of soil sampling were also analyzed. Spatial patterns of distribution of Red Lapacho and its dimensions had completely spatial randomness patterns. Sampled species richness from competitors was of 60 species and the competition generated by them had a random spatial pattern as well. A model for the height – diameter relationship using Generalized Additive Mixed Models (GAMM) produced better results when the latent spatial pattern was included in the model. The spatial patterns of nutrient availability were influenced by relief of the area and distance from the edge of the forest and grassland environments. Anionic nutrients were strongly influenced by the spatial dynamics of the two vegetation types while cations were influenced mainly by pedogenesis. The spatio-temporal Bayesian diameter increment model developed for the Red Lapacho trees showed that there was considerable inter – annual variation in tree growth. The spatial variation in tree growth was closely related to the pedogenesis of the area under study, more specifically, lower increments were observed in areas where the soil had signals of water influence in tits formation. Using site proxies based on geocentric, phytocentric and dendrocentric approaches was able to take into consideration the spatial variation in the growth of Red Lapacho trees and, all approaches may be utilized in the development of growth models.